2018
DOI: 10.3382/ps/pey106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early nutrition and transport of 1-day-old chickens on production performance and fear response

Abstract: The importance of optimal early life conditions of broilers to sustain efficient and healthy production of broiler meat is increasingly recognized. Therefore, novel husbandry systems are developed, in which immediate provision of nutrition post hatch is combined with on-farm hatching. In these novel systems, 1-day-old-chick handling and transport are minimized. To study whether early nutrition and reduced transport are beneficial for broiler performance and behavior, the effects of early or delayed nutrition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 35 publications
2
37
2
2
Order By: Relevance
“…A review of various studies under controlled conditions showed that immediate posthatch feeding significantly improves body weight at slaughter age compared with chickens that have been food deprived for 36 h posthatch or longer, but there is considerable variation between studies ( de Jong et al., 2017 ). For example, Hollemans et al. (2018) observed a higher body weight only until 21 D of age in chickens that were immediately fed posthatch as compared with chickens that were posthatch feed deprived for 54 h. In the present study, the food deprivation period may not have exceeded the period necessary to find long-term effects, for instance because in the particular experiment the distance between hatchery and farm is short resulting in a transport time of only 45 min.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A review of various studies under controlled conditions showed that immediate posthatch feeding significantly improves body weight at slaughter age compared with chickens that have been food deprived for 36 h posthatch or longer, but there is considerable variation between studies ( de Jong et al., 2017 ). For example, Hollemans et al. (2018) observed a higher body weight only until 21 D of age in chickens that were immediately fed posthatch as compared with chickens that were posthatch feed deprived for 54 h. In the present study, the food deprivation period may not have exceeded the period necessary to find long-term effects, for instance because in the particular experiment the distance between hatchery and farm is short resulting in a transport time of only 45 min.…”
Section: Discussionmentioning
confidence: 49%
“…It is very likely that the timing of the first feeding moment affects both performance and welfare ( Willemsen et al., 2010 ; de Jong et al., 2017 ), but the effects of other factors such as day-old chick transport and environmental conditions during hatching on broiler performance and welfare are less clear. Hollemans et al. (2018) showed that day-old chick transport and early nutrition had interactive effects on fearfulness but that transport as such did not affect productivity in broiler chickens that were fed or feed deprived immediately posthatch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight was greater in EN compared with DN chickens throughout the experiment (77 % at 4 d to 39 % at 14 d), as expected (de Jong et al, 2017;Hollemans et al, 2018). Residual yolk weight was evaluated to compare yolk disappearance in EN versus DN broilers.…”
Section: Effects Of Delayed Nutrition On Broiler Growth Performance Amentioning
confidence: 61%
“…While previous literature comprehensively reports the effect of the early environment on adult morphology and physiology (e.g. Alcobendas, Buckley, & Tejedo, 2004; Gutiérrez et al., 2014; Searcy, Peters, & Nowicki, 2004), less studies have focussed on behavioural traits (but see Fox & Millam, 2004; Hollemans, Vries, Lammers, & Clouard, 2018). However, a previous study of Krause et al.…”
Section: Discussionmentioning
confidence: 99%